Address Form in Tiong Pa Creole:An Intercultural Communication Between Chinese and Minangkabau Language - Mac Aditiawarman (Fakultas Sastra Universitas Ekasakti, 2019)
Tiong Pa is an abbreviation of Chinese people in Padang (read the book of Tiong Pa Ethnic in Padang: A Sociolinguistics Perspective written by Aditiawarman, 2005). The language is constructed by elements of the Chinese, Minangkabau, and Indonesian language.The phenomenon of the language formation is caused by communication across cultures engage in continuous communication within long time interaction. One of the communication impact across cultures can be seen among the language community. Communication across cultures influence the language elements such as the address used by Tiong Pa ethnic in Padang.